Antioxidant activity of different fractions from Tinospora crispa stems extracts - Vidhyaa, Parooindran (2012)
"Patawali (Malay) or Tinospora crispa is a plant that has many traditional uses for skin treatment. Tinospora crispa is a woody and glabrous plant in the family MenispermaCeae. In cosmetics, Tinospora crispa can be used externally for its strong antioxidant activity and' free radical scavenging properties. Therefore, the objective of the study was to fractionated all the five fractions from the Tinospora crispa stems extract, to test antioxidant activity of the extracted fractions using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) Assay and finally to evaluate total content of phenolics in the fractions extracted from Tinospora crispa stems. The methodology of the study involves defatting of the plant material, separation and extraction of the moderately polar extract (organic extract) along with the aqueous extract. The fractions are then tested using the DPPH assay for free radical scavenging property to prove its antioxidant activity. The antioxidant activity of the plant fractions are compared with positive control ascorbic acid and butylated hydroxytoulene (BUT). On the other hand, total content of phenolics in fractions extract from the stem was determined using Folin-Ciocalteu method. Moreover, thin layer chromatography method was used to identify phenolics in fraction F3 and fraction F4 while alkaloids were also identified in fraction F4. The research carried out proved that the fractions extracted had significant antioxidant activity especially in fraction F3 and F4, 88.40 ± 0.37 % and 64.91 ± 0.58 % of inhibition repectively which was realatively comparable with the positive control ascorbic acid and butylated hydroxytoluene (BUT). Besides, the total phenolic content in F3 was reported the highest followed by F4, 73.54 ± 2.22 .tg GAE per mg of sample and 62.10 ± 1.42 tg GAB per mg of sample respectively. As an overall conclusion, the research clearly supports that the Tinospora crispa stems extract have significant antioxidant activity due to the presence of phenolics in the fractions that can be further studied. The research too emphasizes the extract from the plant stems to be a good source of herbal medication that can be produced in industries to compliment the society need for curing diseases such as cancer and rapid aging.